Production of a lipase from a pseudomonad species - Smith, Catherine J. (Cranfield University, 1991)
A lipase-producing micro-organism was found to be a strain of Pseudomonas aeruginosa. When it was grown batchwise in a stirred 2 dM3 fermenter in a simple defined minimal salts medium containing yeast extract and glucose, it produced lipase at a level of 0.173 LU/cm3 without the need for a lipid substrate. Batch cultures of cells were fed glucose at constant rates. An optimum rate was found to be 0.50 g/dm3/h and this produced a maximum lipase activity of 0.80 LU/cm3. Medium composition was changed until it was possible to produce 25 g/dm3 dry weight of cells. Evidence of linear growth due to nutient, limitations was obtained. A microcomputer controlled protocol was used successfully to feed glucose solutions at exponentially increasing rates. Problems were encountered with the production of lipase from the interaction with pyocyanin production and from possible trace nutrient limitations.